The Regulatory Region of Muscle-Specific Alpha Actin 1 Drives Fluorescent Protein Expression in Olive Flounder Paralichthys olivaceus - Kong, Hee Jeong (Dev Reprod, 2019)
To develop a promoter capable of driving transgene expression in non-model fish, we identified and characterized the muscle-specific alpha-actin gene in olive flounder, Paralichthys olivaceus (PoACTC1). The regulatory region of PoACTC1 includes putative regulatory elements such as a TATA box, two MyoD binding sites, three CArG boxes, and a CCAAT box. Microinjection experiments demonstrated that the regulatory region of PoACTC1, covering from -2,126 bp to +751 bp, just prior to the start codon, drove the expression of red fluorescent protein in developing zebrafish embryos and hatching olive flounder. These results suggest that the regulatory region of PoACTC1 may be useful in developing a promoter for biotechnological applications such as transgene expression in olive flounder.